In-hospital outcomes of catheter-directed thrombolysis in patients with pulmonary embolism. (25th November 2020) - Hobohm, L; Schmidt, F; Gori, T; Schmidtmann, I; Barco, S; Munzel, T; Lankeit, M; Konstantinides, S.V; Keller, K
Abstract: Background and purpose: Catheter-directed treatment of acute pulmonary embolism (PE) is technically advancing. Recent guidelines acknowledge this treatment option for patients with overt or imminent haemodynamic decompensation, particularly when systemic thrombolysis is contraindicated or has failed. We investigated baseline characteristics and in-hospital outcomes of patients with PE who underwent catheter-directed thrombolysis (CDT) in the German nationwide inpatient cohort. Methods: Data from hospitalizations with PE between 2005 and 2016 were collected by the Federal Office of Statistics (Statistisches Bundesamt) in Germany and included in this analysis. Patients with PE who underwent CDT were compared with patients receiving systemic thrombolysis, and those without thromboytic or other reperfusion treatment. Results: We analyzed data from 978, 094 hospitalized patients with PE. Of these, 41, 903 (4.3%) patients received thrombolytic treatment (systemic thrombolysis in 4.2%, CDT in 0.1%). Among PE patients with shock, CDT was associated with lower in-hospital mortality compared to systemic thrombolysis (OR, 0.29, 95% CI 0.13–0.66, P=0.003). No intracranial bleeding occurred among PE patients with shock who received CDT. Among haemodynamically stable PE patients with right ventricular (RV) dysfunction (intermediate-risk PE), CDT also was associated with a lower risk of in-hospital mortality compared to systemic thrombolysis (OR, 0.52 [95% CI 0.38–0.70]; P<0.001) or no thrombolytic treatment (0.45 [95% CI 0.33–0.62]; P<0.001). Conclusion: In the German nationwide inpatient cohort, CDT was associated with lower in-hospital mortality rates compared to systemic thrombolysis. Prospective controlled data are urgently needed to determine the true value of this treatment option in acute PE. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This study was supported by the German Federal Ministry of Education and Research (BMBF 01EO1503).